(untitled) (Revista Semilleros de Investigación, 2024)
This article analyzes the Bitcoin halving phenomenon and its impact on the price of this cryptocurrency, with a special focus on the event scheduled for April 2024. To achieve this, a mixed-methods approach was applied, combining a literature review and historical data analysis of previous Bitcoin halvings. The results highlight that, although halvings do not produce immediate effects on price, significant value increases are observed in the medium and long term, attributable to the reduction in the issuance rate of new Bitcoins and the perception of scarcity. The analysis also reveals that external factors, such as institutional adoption and global economic conditions, influence market dynamics. It is concluded that halving is a key mechanism in the stabilization and appreciation of Bitcoin, reinforcing its role as a deflationary asset in the digital economy.